(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the demographic characteristics and level of physical activity in patients presenting with heart-related complaints and heart diseases at a tertiary care hospital in Karachi. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the PNS Shifa Hospital, Karachi from January 2021 to July 2021. Materials and Methods: The participants were in-patients enrolled after informed consent. The data was acquired using patient evaluation proforma. The continuous variables were expressed as mean and standard deviation, and the categorical variables were expressed as frequency and percentages. Physical activity level was categorized as a daily walk of more than 30 minutes, 30 minutes or less and infrequent. Results: Out of 79 adult patients, 44 (55.7%) were males and 35 (44.3%) females. There were 35 (44.3%) participants who had comorbidities, the most common being diabetes mellitus and hypertension. Of the 23 (29.1%) participants who had an addiction, 11 (13.9%) took smokeless tobacco and 06 (7.6%) were smokers. Most participants had no formal education [47 (59.5%)]. The occupation profile showed that 36 (45.6%) participants were housewives and 17 (21.5%) retired persons. A large number of participants had infrequent physical activity [48 (60.8%)], which was observed more in females [28 (35.4%)]. Conclusion: Females are more at risk of developing heart diseases due to sedentary life styles and low education, developing disease at an earlier mean age compared to males.